FUNGSI DAN TANTANGAN PENDAMPINGAN PASTORAL BAGI PASIEN WANITA PENDERITA PENYAKIT KANKER DI YAYASAN CAC (CANCER AWARENESS COMMUNITY) SURABAYA - Elfrida Hutagalung; Anggia Hapsari; Johannes Rajagukguk (Bethel Press, 2021)
A person who experiences the deadly disease of cancer tends to be frustrated and desperate to get out of the disease. In addition to the small chance of healing, the cost of treatment and therapy is very expensive so that only certain groups can access it. The Surabaya CAC Foundation is one form of service that answers this problem. Cancer patients are served not only medically, but they also provide assistance by bringing in God's servants and counselors to accompany them. They help by providing temporary shelter and medical expenses as much as they can afford. The purpose of this study is to obtain a model of pastoral care for cancer patients at CAC Surabaya which can later be applied in general. The method used is qualitative with the data source is in-depth interviews with patients and managers of the Surabaya CAC Foundation. The results showed that the function of pastoral assistance is in reconciliation, healing, and affirmation. Meanwhile, the challenges of pastoral care for patients can be seen when it raises the spirit and hope of the patient's life, convinces the patient that miracles still exist, leads the patient to believe in the power of prayer, and awakens the patient's faith through the Words of God.